Ludomania as a threat to the state security. Social, economic and legal contexts - Oliynychuk, Oleksandra; Khomiuk, Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
This article discusses the game addiction as a threat to the security of the state. Investigated problem is very heterogeneous and its solution requires a comprehensive approach. Given this, the research of ludomania from the position of the state security is extremely relevant and prospective. The purpose of the article is to investigate social, economic and legal issues related to gambling addiction, as well as to clarify the author’s proposals to minimize the impact of ludomania on the security of the state.In the article there was noted that game mania is a manifestation of deep psychological problems. It arises because of the impossibility of self-realization, the achievement of the goal. Thereby, game mania was described as a social problem. The stages of gambling addiction were considered in the article. The current state of legal regulation of gambling business in Ukraine was analyzed. So, in Ukraine there are gambling bans and criminal liability for gambling operate, but underground casinos and other gambling establishments still operate because of fuzzy legality in regulation, “cover” of gambling business by law enforcement agencies and dependence of people on gambling. After all, services exist as long as they are of interest to consumers and this is profitable.The lack of clear legal regulation of gambling (legal problem) forms a favorable basis for the activity of illegal business entities and uncontrolled attraction of emotionally unstable persons, prone to addiction, with all future consequences of ludomania (social problem). In addition, the spread of corruption and the criminalization of the economy and, accordingly, the reduction of the level of economic security of the state (economic problem) are observed. Given this, a model of influence of illegal gambling on the level of economic security of the state was developed. The expediency of legalizing the gambling infrastructure, which should be accompanied by the creation and support of activities that are socially significant for citizens, was substantiated. Gambling regulation measures in Ukraine, based on successful world experience in combating the spread of gambling addiction, were proposed.